Requirement derivation of vehicle steering using mechanical four-poles in the presence of nonlinearities. (16th June 2021) - Muenster, M.; Lehner, M.; Rixen, D.
Highlights: Vehicle subsystem dynamics can be characterized in the frequency domain by mechanical four-poles. Four-pole coefficients are suitable to derive requirements to subsystem dynamics. Subsystem identification is feasible in practice either experimentally or virtually. The method is applicable to problems with limited knowledge about desirable subsystem and system dynamics. The method is applicable to nonlinear systems whose dynamics depends on the input force level. Abstract: In a recent companion publication, we developed the basic theory for deriving requirements for the dynamic properties of vehicle components. These requirements correspond to targets at vehicle level, but they address stand-alone subsystems being developed simultaneously by different parties. For this purpose, the vehicle, i. e., the coupled system, is divided into subsystems such as the steering and the front axle. The substructuring method used for this was based on the four-pole theory, where frequency-dependent transfer matrices are needed. Thereby, the relevant transfer coefficients of each subsystem were assumed to be linear. In this work, the method is extended to cope with nonlinear behavior of the subsystems. The basic idea is to characterize the nonlinear systems in the frequency domain by their mono-harmonic responses depending on the force level acting at their input. Both virtual and experimental methods can be used to identify the target-relevant four-pole model of the steering and the front axle. To consider nonlinearities in terms of amplitude-dependent behavior, each subsystem is investigated at multiple amplitude levels. As a main difference to the companion publication, the results are not limit curves, but rather limit surfaces in terms of the dynamics of each subsystem over frequency and force amplitude, which serve as envelope to subsystem design. Iterative algorithms are proposed to make the linear four-pole method still applicable to problems with this kind of nonlinearity where higher harmonics resulting from the nonlinearities can be neglected.